KEDUDUKAN ANAK DARI PERKAWINAN TIDAK TERCATAT DI INDONESIA - Puspitasari, Ratna (UIR Press, 2023)
The rights, obligations and responsibilities of children towards their families continue continuously throughout the lives of the children and their parents according to positive law and religious or belief law. . The status and position of the child is whether the state recognizes it or not in positive legal terms. Differences in legal protection for children legally exist, although this does not ignore the status and position of children born from unregistered marriages, but only relates to the protection system and resolving legal problems which contain other meanings of administrative and positive legal protection only. Children from unregistered marriages receive civil and public legal guarantees and protection from their mothers and their mothers' families, not from their fathers and their father's families. This research uses positive legal and religious studies as well as qualitative descriptive research methods with findings that legally children born out of wedlock can obtain rights like legitimate children but must fulfill requirements, one of which is legal recognition from the parents who seeded or impregnated the mother.